P584 Factors predicting lifetime sexual experience among rural, reservation-based native american youth. (14th July 2019) - Tingey, Lauren; Chambers, Rachel; Rompalo, Anne; Beach, Anna; Melgar, Laura; Rosenstock, Summer; Lee, Angelita
Abstract : Background: Early sexual initiation is a risk factor for sexually transmitted infection and unintended pregnancy. Native American youth initiate sex earlier than other U.S. youth contributing to current inequalities in sexual health. Identifying factors that predict lifetime sexual experience among Native youth can inform the development of primary prevention programming to delay sexual initiation and improve sexual health outcomes in this population. Methods: We analyzed cross-sectional data from 558 Native youth ages 11–19 from a rural, reservation-based community. Multivariate logistic regression models were used to estimate associations between lifetime sexual experience (vaginal and/or anal sex) and independent variables across eight categories: sociodemographic, knowledge, attitudes/perceptions, beliefs, intentions, skills, behaviors, and theoretical constructs. Results: The sample was 51.6% female, mean age 13.4 years ( SD =1.9); and 8.0% were sexually experienced. In our final model, older age (OR=2.04; p<0.0001) and identifying as transgender (OR=35.3; p=0.019) predicted lifetime sexual experience. The notion that sometimes sex just happens (OR=0.56; p=0.01), and having condom use self-efficacy (OR=0.47, p=0.026) were negatively associated with lifetime sexual experience. Youth who intended to have sex in the next 6 months were more likely to be sexually experienced (OR=3.18; p<0.0001). Recent substance use including having smoked cigarettes (OR=4.38, p=0.048), and having smoked marijuana in the past 3 months (OR=6.48, p=0.002) predicted lifetime sexual experience. Conclusion: Results provide direction for future programming. Programs focusing on intentions to have sex while cultivating skills to promote condom use, in addition to being delivered stratified by age, may have the greatest impact. Substance use was a driving factor in sexual initiation; thus, sexual health education programs should simultaneously target substance use prevention. That identifying as transgendered predicted sexual experience is notable: despite research indicating transgendered youth of other ethnicities have heightened risk for negative sexual health outcomes, little research has been conducted with transgendered Native youth. Disclosure: No significant relationships.